Screening of natural compounds inhibiting biofilm formation by antibiotic resistant enterobacteria using experimental trials and computational molecular modelling - Cosa, Sekelwa (University of Pretoria, 2024)
Dissertation (MSc (Bioinformatics))--University of Pretoria, 2024.